Mathematical analysis and applications selected topics - Ruzhansky, M.; Dutta, Hemen; Agarwal, Ravi P. (Wiley, 2018)
"Mathematical Analysis and Applications: Selected Topics offers the theories, methods, and applications of a variety of targeted topics including operator theory, approximation theory, fixed point theory, stability theory, minimization problems, many-body wave scattering problems, Basel problem, Corona problem, inequalities, generalized normed spaces, variations of functions and sequences, analytic generalizations of the Catalan, Fuss, and Fuss-Catalan Numbers, asymptotically developable functions, convex functions, Gaussian processes, image analysis, and spectral analysis and spectral synthesis. The authors--a noted team of international researchers in the field-- highlight the basic developments for each topic presented and explore the most recent advances made in their area of study. The text is presented in such a way that it enables the reader to follow subsequent studies in a burgeoning field of research." -- Back cover.